2014
DOI: 10.1371/journal.pone.0095920
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 Is a Potential Biomarker of HIV/AIDS Disease Progression and Therapy

Abstract: BackgroundThe surrogate markers of HIV/AIDS progression include CD4 T cell count and plasma viral load. But, their reliability has been questioned in patients on anti-retroviral therapy (ART). Five microRNAs (miRNAs) - miR-16, miR-146b-5p, miR-150, miR-191 and miR-223 in peripheral blood mononuclear cells (PBMCs) were earlier found to assign HIV/AIDS patients into groups with varying CD4 T cell counts and viral loads. In this pilot study, we profiled the expression of these five miRNAs in PBMCs, and two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…It has been observed that HIV infection causes changes in the profile of some miRNA such as miR-29a, miR-29b, miR-125b, miR-223, miR-382, miR-198, etc. This changes have been observed in infected CD4 + T cell, PBMCs or serum [1][2][3]6,[8][9][10][19][20][21]. However, it should be taken into account that miRNAs may be regulated in different ways providing different profiles depending on the different immune compartments.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…It has been observed that HIV infection causes changes in the profile of some miRNA such as miR-29a, miR-29b, miR-125b, miR-223, miR-382, miR-198, etc. This changes have been observed in infected CD4 + T cell, PBMCs or serum [1][2][3]6,[8][9][10][19][20][21]. However, it should be taken into account that miRNAs may be regulated in different ways providing different profiles depending on the different immune compartments.…”
mentioning
confidence: 95%
“…Editorial microRNAs (miRNAs) are non-coding RNAs (19-25 nucleotides) that regulate gene expression at transcriptional level [1][2][3][4][5][6]. They bind to messenger RNAs (mRNA), generally by imperfect base alignment in 3'-UTR region, and cause translational repression, mRNA destabilization and/or mRNA direct destruction [3][4][5].…”
mentioning
confidence: 99%
See 3 more Smart Citations